IL-33/sST2 axis in The Cardiovascular System: A Brief Review - Negar Firouzabadi; Maryam Dashti (Shiraz University of Medical Sciences, 2020)
IL-33 is a type of cytokine and a new member of the IL-1 family labeled as an alarmin, which is released under stressful settings. IL-33 is a biomechanically induced protein and is mainly produced by cardiac fibroblasts and is expressed by various cell types after pro-inflammatory stimulation. Although the physiological role of IL-33 as a nuclear factor is not fully understood, it seems to be involved in transcriptional suppression via binding to nucleosomes and regulating the density of chromatins. It can play different roles, from progression to protection against a disease, depending on the type of the disease. Its signaling happens by means of the sST2 receptor. sST2 is a mechanically induced protein of the cardiac muscle. The IL-33/ST2 axis plays an important role in various illnesses such as cardiovascular diseases and can be a potential target for disease treatment. This review provides an overview of different aspects of IL-33 and its related receptor, sST2 along with the role of IL-33/sST2 axis in different cardiovascular diseases.